Therapeutic Jurisprudence in Swift and Certain Probation. (November 2020) - Frailing, Kelly; Alfonso, Brandi; Taylor, Rae
While the manifestation of therapeutic jurisprudence in specialty courts such as mental health and drug courts has received attention in the literature, there is little scholarship on the manifestation and function of therapeutic jurisprudence in probation settings. This study examines therapeutic jurisprudence in the context of a HOPE-based probation program called Swift and Certain probation. We observed status hearings and surveyed participants on their perceptions of the program for over 2 years. We found that therapeutic jurisprudence was manifested in the judge's liberal use of praise during status hearings, which appeared to be an important part of participants' positive perceptions of him and of procedural justice more generally. It was also manifested, though less directly, in interactions and relationships participants have with their probation officers. We conclude with suggestions for the implementation of therapeutic justice practices in Swift and Certain and similar probation programs.